2021
DOI: 10.1515/dx-2021-0046
|View full text |Cite
|
Sign up to set email alerts
|

An overview of mental health during the COVID-19 pandemic

Abstract: Since its initial outbreak in late 2019, the COVID-19 pandemic has profoundly affected the global community. In addition to the negative health consequences of contracting COVID-19, the implementation of strict quarantine and lockdown measures has also disrupted social networks and devastated the global economy. As a result, there is rising concern that the pandemic has taken a toll on the mental health of the general population. To better understand its impact, an increasing number of studies examined the eff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
51
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 99 publications
5
51
1
4
Order By: Relevance
“…Loneliness is a signi cant public health issue and associated with a wide range of health outcomes, such as mental health problems, substance use and physical health conditions [43]. Our ndings correspond with earlier studies performed during the pandemic that have demonstrated an increase in prevalence of loneliness and social disconnection over that time [44]. However, even though a negative change was seen among parents in our study, the association with HRQOL was not signi cant.…”
Section: Discussionsupporting
confidence: 84%
“…Loneliness is a signi cant public health issue and associated with a wide range of health outcomes, such as mental health problems, substance use and physical health conditions [43]. Our ndings correspond with earlier studies performed during the pandemic that have demonstrated an increase in prevalence of loneliness and social disconnection over that time [44]. However, even though a negative change was seen among parents in our study, the association with HRQOL was not signi cant.…”
Section: Discussionsupporting
confidence: 84%
“…60.7/ 100,000) in the world (Ritchie et al, 2020).The quarantine measures of self-isolation may have affected the social relationships of those whose only social contact was out of the home. These restriction measures have also broadened a range of mental health problems associated with the COVID-19 pandemic, including symptoms of anxiety and depressive disorders, posttraumatic stress disorder (PTSD), loneliness, stress, and psychological distress in the general population (Chen et al, 2021;Li et al, 2020;Vindegaard & Benros, 2020;Xiong et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Countries scramble to contain the virus spread and "flatten the curve" to prevent total meltdown of their health care systems either by instituting full or partial lockdowns and strict border restrictions before an effective vaccine or treatment can be developed to lessen the impact of the virus' devastation on human lives. Not only have these extreme measures on curtailing physical human interactions come at an enormous socioeconomic cost [3], they also have a significant, far-reaching impact on every aspect of our lives [4], including our mental health [5], as we pit life against human liberty [6].…”
Section: Introductionmentioning
confidence: 99%